Reconstruction of Humanistic Learning Theory in the Context of Islamic Education: Integrative Islamic Humanistic Learning as a New Paradigm for Islamic Education Learning - Mujahid; Muqowim (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose – This research aims to reconstruct humanistic learning theory within the framework of Islamic education. Humanistic theory has often been viewed as a product of secular thought that is not aligned with Islamic values. However, several studies have shown the potential for integration between humanistic approaches and Islamic education, although these are still partial and lack a comprehensive conceptual framework. This research seeks to fill this gap by offering a more holistic, integrative framework. Design/methodology/approach – This research uses a qualitative approach with a philosophical-conceptual design. Data were obtained through a purposive literature review of reputable books and scientific articles relevant to humanistic learning theory and Islamic education. Analysis was conducted using interpretive and content analysis techniques to identify key concepts, philosophical assumptions, and common ground between the two perspectives. Findings – The research results show that humanistic learning theory can be reconstructed from an Islamic educational perspective through a theocentric-humanistic approach that integrates cognitive, spiritual, and behavioral dimensions. This research produces a conceptual model. Integrative Islamic Humanistic Learning that combines Tauhid (foundation), Ilmu (rationality), Zikir (spirituality), and Amal (practice) . Belief in the oneness of God (foundation), knowledge (rationality), remembrance of God (spirituality), and righteous action (practice). Research implications/limitations – This research is conceptual in nature and does not include empirical validation, so the findings are not intended to be directly generalized. Therefore, further research is needed to test the implementation and effectiveness of the proposed model in real-world learning contexts. Originality/value – This research contributes by providing a philosophical reconstruction of humanistic learning theory in the context of Islamic education. The proposed model bridges the gap between the secular humanistic perspective and Islamic educational values, opening new directions for the development of more holistic and transformative learning.